Agrifood systems policy research: historical evolution of agrifood systems in Bangladesh - Sarkar, Anindita (International Water Management Institute (IWMI). CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2023)
This study presents evidence from secondary literature and archival sources on how the current agrifood systems in Bangladesh were developed and the obstacles and opportunities that have influenced their transformation since the 1850s. It lays out the politico-economic context of these systems, allowing for a comprehensive understanding of their current state.